“Do Doctors and Patients Have Different Understandings of Pain?” – A Pilot Study of Different Perspectives and Understandings of Pain in Clinical Pain Research - Gormsen LK (Journal of Pain Research)
Lise Kirstine Gormsen1,2 1Department of Functional Disorders, Aarhus University Hospital, Aarhus, Denmark; 2Department of Clinical Medicine, Faculty of Health, Aarhus University, Aarhus, DenmarkCorrespondence: Lise Kirstine Gormsen, Department of Functional Disorders, Aarhus University Hospital and Department of Clinical Medicine, Faculty of Health, Aarhus University, Palle Juul-Jensens Boulevard 11, Aarhus, 8200, Denmark, Email lise.gormsen@clin.au.dkBackground and Objective: Ambiguous results on pain thresholds often occur from biomedical pain research. Although results and methods are frequently discussed, only few studies have investigated participants’ understanding and perspectives of pain in research settings. The aim of this qualitative pilot study was to explore different understandings of pain in a clinical pain research setting.Methods: We briefly interviewed 25 subjects, including Danish pain doctors and psychiatrists as well as pain patients, depressed patients, and healthy controls (five in each group) about their understanding of pain.Results: Laymen seem less inclined to verbalize pain than professionals. In addition, they may embrace a concept of suffering that goes beyond the traditional body–mind dichotomy. Since suffering may be part of the pain experience, this difference in the understanding of pain may be at the core of the often ambiguous results when doctors and other health professionals study pain.Conclusion: The results emphasize the need for supporting the ongoing process of integrating broad perspectives on pain in clinical pain research, including the concept of suffering. More research and resources are needed in this particular area of pain medicine.Keywords: pain, suffering, concepts of pain, clinical pain research, pain thresholds